Pengaruh Jumlah Penduduk, Jumlah Wisatawan dan Inflasi terhadap Penerimaan Pajak Restoran di Kota Banjarmasin - Ratu Ayu Nurseptiawan; Muhammad Rusmin Nuryadin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to measure the strength of the relationship between population, number of tourists, and inflation on restaurant tax revenues in Banjarmasin City. The scope of the research is restaurant tax in Banjarmasin City using multiple linear regression analysis with quantitative descriptive data collection techniques taken from secondary data sourced from the literature and official data.The results of this study ashowthat there is a joint influence between the number of residents, the number of tourists, and inflation on restaurant tax revenues in Banjarmasin City. While partially only the population has a positive and significant influence.